Robust Suppression of HIV Replication by Intracellularly Expressed Reverse Transcriptase Aptamers Is Independent of Ribozyme Processing - Lange, Margaret J (Nature Publishing Group, 2012)
RNA aptamers that bind human immunodeficiency virus 1 (HIV-1) reverse transcriptase (RT) also inhibit viral replication, making them attractive as therapeutic candidates and potential tools for dissecting viral pathogenesis. However, it is not well understood how aptamer-expression context and cellular RNA pathways govern aptamer accumulation and net antiviral bioactivity. Using a previously-described expression cassette in which aptamers were flanked by two “minimal core” hammerhead ribozymes, we observed only weak suppression of pseudotyped HIV. To evaluate the importance of the minimal ribozymes, we replaced them with extended, tertiary-stabilized hammerhead ribozymes with enhanced self-cleavage activity, in addition to noncleaving ribozymes with active site mutations. Both the active and inactive versions of the extended hammerhead ribozymes increased inhibition of pseudotyped virus, indicating that processing is not necessary for bioactivity. Clonal stable cell lines expressing aptamers from these modified constructs strongly suppressed infectious virus, and were more effective than minimal ribozymes at high viral multiplicity of infection (MOI). Tertiary stabilization greatly increased aptamer accumulation in viral and subcellular compartments, again regardless of self-cleavage capability. We therefore propose that the increased accumulation is responsible for increased suppression, that the bioactive form of the aptamer is one of the uncleaved or partially cleaved transcripts, and that tertiary stabilization increases transcript stability by reducing exonuclease degradation.